An empirical analysis of green convention attendees' switching intentions. Issue 3 (3rd July 2017) - Wu, Hung-Che; Cheng, Ching-Chan; Hong, Wien
ABSTRACT: This study aims at proposing to test a research model to gain a better understanding of the relationships among the dimensions of experiential quality, green experiential satisfaction, green alternative attractiveness, green service fairness, green variety-seeking, and green switching intentions. The study's findings are based on structural equation model analysis of a convenience sample of 650 attendees at the 13th International Green Building and Energy-Savings Exhibition 2016 in Chongqing, China. The results of this analysis contribute to the services marketing theory by providing additional insights into green switching intentions, the dimensions of experiential quality, green experiential satisfaction, green alternative attractiveness, green service fairness, and green novelty-seeking. The study's results will assist green convention management in developing and implementing market-orientated service strategies to increase the dimensions of experiential quality and green experiential satisfaction, enhance green alternative attractiveness, green service fairness, and green novelty-seeking, and decrease green switching intentions.